Through-life stochastic carbon emission assessment and optimisation for critical assets - Townley, Matt; Salonitis, Konstantinos (Elsevier, 2023)
International governments and businesses are increasingly pledging more action to address human-induced climate change, including committing to the Paris Climate Agreement, which seeks to reduce global Greenhouse Gas Emissions (GHGE). Critical assets provide essential capabilities where failure could have catastrophic consequences. These assets have long service lives and are exposed to varying operational conditions and service requirements, which makes assessing through-life GHGE challenging. Current modelling techniques provide deterministic, single-point results, which provides a limited assessment of critical asset through-life GHGE where uncertainty can be significant. Furthermore, no modelling technique was identified that relates asset GHGE to Whole Life Cost (WLC) and operational effectiveness, which are both organisational priorities. This leaves decision-makers without robust information regarding the possible impacts of GHGE reduction strategies on the WLC and the operational effectiveness of their critical assets. This study develops a methodology framework to model critical asset GHGE with WLC and operational availability based on industry best practices and transferrable modelling techniques from other sectors. A model was created based on an in-service helicopter platform and was subjected to four test scenarios to demonstrate effects on WLC, GHGE and operational availability relative to baseline. Monte Carlo simulation was used to appropriately present modelling uncertainty.
Keywords: Greenhouse gas emissions modelling; Carbon modelling; Monte Carlo; Whole life cost; Life cost modelling; Operational availability; Helicopter carbon emissions